Agregação de valor a resíduos agroindustriais: produção de enzimas oxidativas por basidiomicetos e aplicação na descoloração de corantes industriais - Bazanella, Gisele Cristina dos Santos (2013)
Large amounts of chemical dyes are used for various industrial applications such as textile and printing industries. It is estimated that between 10 and 20% of about 0.7 million tons of dyestuff that are manufactured each year and used in dyeing processes may be found in wasterwater. Several of these dyes are very stable to light, temperature and microbial attack, making them recalcitrant compounds. Dyes can obstruct the passage of the sunlight through the water resources, leading to decreased photosynthesis by aquatic plants coupled to a decreased concentration of dissolved oxygen, and to a diminished biodegradation of organic matters. Currently the removal of dyes from the effluents is brought about by physicochemical means, including adsorption, precipitation, coagulationflocculation, oxidation, filtration and photo-degradation. At the present, the biotechnological approaches are proven to be potentially effective and ecoefficient in the treatment of these pollution sources. Several microorganisms including the ligninolytic fungi have the ability to decolorize and degrade a wide range of dyes. The possibility of using the filamentous fungi associated with the decay of wood, usually called white-rot fungi, has attracted considerable attention. White-rot fungi possess a group of oxidative enzymes named lignin-modifying enzymes or ligninolytic enzymes involved in lignin degradation, mainly laccases and peroxidases. Due to the fact that ligninolytic enzymes are non-specific, they are able to attack a series of molecules chemically similar to lignin including the synthetic dyes. In the first paper, a review of implication of white-rot fungi and their ligninolytic enzymes in dye decolorization processes was carried out. In the second article, the production of ligninolytic enzymes (laccase and Mn dependent peroxidase) by the white-rot fungus Pleurotus pulmonarius (FR.) Quélet was studied in solid state cultures using agricultural and food wastes as substrate. The highest activities of laccase were found wheat bran (2,860±250 U/L), pineapple peel ( 2,450±230 U/L) and orange bagasse (2,100±270 U/L) cultures, all of them at an initial moisture level of 85%. The highest activities of Mn peroxidase were obtained in pineapple peel cultures (2,200±205 U/L) at an initial moisture level of 75%. In general, the condition of high initial moisture level (80-90%) were the best condition to laccase activity, while the best condition to Mn peroxidase activity was cultivation at low initial moisture (50-70%). Cultures containing high Mn peroxidase activities were more efficient in the decolorization of the industrial dyes congo red, methylene blue and ethyl violet than those containing high laccase activity. Also, crude enzymatic extracts with high Mn peroxidase activity were more efficient in the in vitro decolorization of methylene blue, ethyl violet and congo red. The dye remazol brilliant blue R (RBBR) was efficiently decolorized by both crude extracts, rich in Mn peroxidase activity or rich in laccase activity. Finally, in the third article, the production of laccase by Pleurotus ostreatus was evaluated in solid-state cultivation using Moringa oleifera seed and wheat bran as substrate in the presence and absence of activated charcoal as a clarifying agent. The results show that high laccase activity was obtained in cultures with M. oleifera (2338 ± 220 U/L) compared to those obtained with traditional wheat bran substrate (1520 ± 285 U/L). The presence of the clarifying agent activated carbon had a significant effect on the laccase production cultures in wheat bran (2081a,b ± 202 U/L) but not in the cultures with M. oleifera (2126a,b ± 48 U/L). The use of a mixture of bran seed of Moringa in 4:1 ratio also resulted in a small increase in the production of lacase (2252a,b ± 475 U/L). The activated charcoal showed a clarifying effect on crude enzyme extract obtained from cultures in M. oleifera. Laccase obtained in seed crops with M. oleifera plus 1% activated carbon was concentrated by membrane filtration with 5 kDa cut off followed by lyophilization and used successfully in decolorization of the anthraquinone dye RBBR.